The effects of an in-season athletic motor skill competencies intervention on physical bio-motor qualities among elite youth soccer players - Synott, G.; Byrne, P.; Lisa, R.; Moody, J.; Duggan, J. (International Journal of Strength and Conditioning, 2025)
The aim of this study was to evaluate the efficacy of an in-season athletic motor skill competency (AMSC) programme on the physical bio-motor qualities of youth academy soccer players. Thirty-four (n = 34) U14 and U15 male underage academy soccer players were recruited from a League of Ireland (LOI) soccer club. The study was conducted over 10 weeks that included a pre-testing battery, an 8-week intervention, and a post-testing battery. Pre- to post-intervention, the U14 squad experienced significant increases in countermovement jump (CMJ) peak power, and both chin-up three repetition maximum (3RM) and predicted 1RM (p < 0.05, effect size [ES] = 0.15 to 0.25). The U15 squad displayed significant changes in 5m sprint time (p < 0.05, ES = 0.20); CMJ height, peak power, and propulsive impulse (p < 0.05, ES = -0.17 to -0.58). The U15 squad demonstrated a significant improvement in their 5m sprint time compared to the U14 squad (p < 0.05). Additionally, 38% of the U14 squad showed improvements exceeding the smallest worthwhile change (SWC) across seven CMJ variables (jump height, peak power, eccentric duration, RSImod, mean peak force, propulsive impulse, time to take-off). Similarly, 43% of the U15 squad achieved positive changes greater than the SWC in sprint speed, strength, and 5 of the jump variables. This study provides valuable evidence for integrating an AMSC programme into youth soccer training regimens to optimize player development and performance.